2010
DOI: 10.1007/s00122-010-1275-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of quantitative trait loci controlling pre-harvest sprouting resistance by using backcrossed populations of japonica rice cultivars

Abstract: Backcrossed inbred lines (BILs) and a set of reciprocal chromosome segment substitution lines (CSSLs) derived from crosses between japonica rice cultivars Nipponbare and Koshihikari were used to detect quantitative trait loci (QTLs) for pre-harvest sprouting resistance. In the BILs, we detected one QTL on chromosome 3 and one QTL on chromosome 12. The QTL on the short arm of chromosome 3 accounted for 45.0% of the phenotypic variance and the Nipponbare allele of the QTL increased germination percentage by 21.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 45 publications
3
72
0
Order By: Relevance
“…To confirm the effect of each haplotype on resistance to M. oryzae, we used 6 backcrossed lines, each carrying the target chromosome from 1 of 6 donors: Hokkai 188 (BC 4 F 4 ), Padi Kuning (BC 2 F 2 ), LAC23 (BC 4 F 4 ), IR64 (BC 4 F 4 ), Bleiyo (BC 4 F 3 ), or Nipponbare (BC 4 F 4 ). The lines for LAC23 (SL2207), IR64 (SL2003), and Nipponbare (SL602) were used in previous studies [52][53][54] .…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the effect of each haplotype on resistance to M. oryzae, we used 6 backcrossed lines, each carrying the target chromosome from 1 of 6 donors: Hokkai 188 (BC 4 F 4 ), Padi Kuning (BC 2 F 2 ), LAC23 (BC 4 F 4 ), IR64 (BC 4 F 4 ), Bleiyo (BC 4 F 3 ), or Nipponbare (BC 4 F 4 ). The lines for LAC23 (SL2207), IR64 (SL2003), and Nipponbare (SL602) were used in previous studies [52][53][54] .…”
Section: Methodsmentioning
confidence: 99%
“…These analyses have identified several unique QTLs for heading date (Matsubara et al 2008), culm length (Hori et al 2009), pre-harvest sprouting resistance (Hori et al 2010), and eating quality (Takeuchi et al 2008;Kobayashi and Tomita 2008;Wada et al 2008). The success of this approach implies that the use of a wide range of cross combinations might increase the opportunity to detect unique QTLs.…”
Section: Comparison With Qtl Clusters Identified In Other Studiesmentioning
confidence: 99%
“…The results of this study revealed that a QTL for heading date, qDTH3, was linked to qLTG3-1. Furthermore, QTLs for agronomically important traits, eating quality (Kobayashi et al 2008, Takeuchi et al 2008, Wada et al 2008) and pre-harvest sprouting resistance (Hori et al 2010), have been identified in this chromosomal region. For the manipulation of these traits, targeted recombination within this chromosomal region should be useful for creating novel genotypes, which may provide novel advantages for adaptation for local environmental conditions.…”
Section: Discussionmentioning
confidence: 99%